RELIGIOUS BATHING MONUMENTS WITH FEMALE DEITY STATUES IN INDONESIA - AN ARCHAEOLOGICAL PERSPECTIVE - Sakai, Takashi (The Indonesian Journal of Social Studies, 2025)
This study aims to understand the development of Java-Balinese religious bathing monuments/petirtaan from the point of view of comparative archaeology in particular the structural changes of the fountain system with female deity statues. Firstly, I have divided the major monuments into two categories based on the condition of the spout, and each category was respectively classified into five types according to basic forms. By comparing similar water monuments in Angkor and India, I considered the meaning of the transformation of these monuments during the Central and East Java periods, and hypothetically discussed the birth of female deity statues as fountain spouts.